Synaptic network structure shapes cortically evoked spatio-temporal responses of STN and GPe neurons in a computational model - Kromer, Justus A.; Bokil, Hemant; Tass, Peter A. (Frontiers in Neuroinformatics, 2023)
The basal ganglia (BG) are involved in motor control and play an essential role in movement disorders such as hemiballismus, dystonia, and Parkinson's disease. Neurons in the motor part of the BG respond to passive movement or stimulation of different body parts and to stimulation of corresponding cortical regions. Experimental evidence suggests that the BG are organized somatotopically, i.e., specific areas of the body are associated with specific regions in the BG nuclei. On the other hand, signals related to the same body part that propagate along different pathways converge onto the same neurons in the BG. This leads to characteristic shapes of cortically evoked responses. It also furthers the idea of the existence of functional channels that allow for the processing of different motor commands or information related to different body parts in parallel. Neurological disorders such as Parkinson's disease are associated with pathological activity in the BG, and impaired synaptic connectivity together with reorganization of somatotopic maps. A widely accepted hypothesis is that motor symptoms are, at least partly, caused by an impairment of network structure that perturbs the organization in functional channels. We develop a computational model of the STN-GPe circuit, a central part of the BG, that reproduces experimentally observed cortically evoked responses. We study how these responses are affected by changes in the network structure. Based on our findings, we suggest a two-site stimulation protocol to measure and quantify the organization of the BG in the form of functional channels and how these channels may be affected by neurological disorders in experiments. The presented results provide insight into the organization of BG synaptic connectivity, which is important for the development of computational models. Our work may motivate further experiments to analyze the network structure of BG nuclei and their organization in functional channels.